PENGARUH NET PROFIT MARGIN (NPM) DAN PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM PADA PT SUMBER ALFARIA TRIJAYA TBK TAHUN 2013-2022 - Amelia, Mela; Bayu Ganar, Yulian (Journal of Research and Publication Innovation, 2024)
This research aims to analyze the effect of Net Profit Margin (NPM) and Price Earning Ratio (PER) on stock returns of PT Sumber Alfaria Trijaya Tbk. for the period of 2013-2022. The data used is secondary data obtained from the company's annual financial reports published on the Indonesia Stock Exchange. The research method used is a quantitative method with an associative approach. The data analysis technique used is multiple linear regression analysis. The results of the study show that the Net Profit Margin (NPM) variable partially has a very strong and significant positive relationship with stock returns with a Thitung (4.116) value > Ttabel (2.364) with a significance level of (0.004) < 0.05 and a multiple correlation test value of 0.843. The Price Earning Ratio (PER) variable partially has a very strong and significant positive relationship with stock returns with a Thitung (2.406) value > Ttabel (2.364) with a significance level of (0.047) < 0.0505 and a multiple correlation test value of 0.843. The Net Profit Margin (NPM) and Price Earning Ratio (PER) variables simultaneously have a significant effect on stock returns with an Fhitung value of 8.570 and an Ftabel value of 4.737 (8.570 > 4.737) and a significance value of less than 0.05 (0.013 < 0.05). Supported by the results of the correlation coefficient test which produces a value of 0.843 and the results of the coefficient of determination test (R2) of 71%, and the remaining 29% is influenced by other variables that are not included in this study. This means that the two variables together have an effect on stock returns.